فعّالية استخدام الحاسوب في تعليم اللغة العربية لتنمية مهارة الكلام بالصف التاسع ب بالمدرسة دار السلام جومبانج: Efektivitas Penggunaan Komputer dalam Pengajaran Bahasa Arab untuk Meningkatkan Keterampilan Bicara di Kelas IX B MTs Darussalam Jombang - Luthfi, Ibnu Mas'ud (Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
Therefore, facing similar problems, it becomes a necessity for teachers to be able to express their innovation and creativity to create and design teaching strategies that are more interesting and in line with needs and objectives so that they can create a more effective and enjoyable teaching and learning process, one the other is using computers as a teaching medium. Problem formulation: "To what extent is the effectiveness of using computer media in teaching speaking skills at MTS Darussalam?" This research is a type of classroom action research (PTK) which consists of four stages, namely planning, implementation, observation, reflection, and lasts two cycles. The research population was all MTS Darussalam students with a sample of class IX B students for the academic year. Meanwhile, the data collection techniques used by researchers are observation, interviews, and speaking skills tests. The results of the research show that the use of computers as a teaching medium has proven effective in improving the speaking skills of class IX students at Mts Darussalam by looking at the fact that the students' learning motivation has increased which ultimately influences increasing their speaking abilities. Students' ability and proficiency in speaking increased as we can see in table VII in this table, showing that the oral test results of all students were higher than the minimum learning completion standard (SKM) in the field of Arabic language studies. This evidence shows that all students have been successful in learning speaking skills.